Physical characteristics of the Chief Executive Officer and firm accounting and market-based performance - Ur Rahman, Haseeb; Mohd. Yussoff Ibrahim,; Ayoib Che Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Despite the key role of the Chief Executive Officer (CEO), extant literature pays little attention to the physical characteristics of the CEO. Therefore, this paper investigates certain physical characteristics - such as age, gender, ethnicity and nationality of the CEO in relation to accounting (ROE) and market-based (market value) firm performance. The paper applies OLS with robust standard errors to a panel composed of 1600 firm-year observations of non-financial Malaysian listed companies between 2010 and 2014. The results reveal that the ethnicity (Chinese) and nationality (foreign) of a CEO have a significant positive association with both proxies of firm performance, while the age of the CEO has no significant effect. Moreover, a female CEO has an insignificant and significant positive relation with ROE and firm market value, respectively. Alongside contributing to the limited literature that exists in relation to the subject, the paper provides important insights for regulators, shareholders, investors, banks, corporate boards and financial institutions in regards to the evaluation of firms and the allocation of economic resources.